PENGEMBANGAN KARTU BUDAYA INDONESIA (KABUSA) PADA KELAS IV SEKOLAH DASAR - Cahyati, Intan; Dian Lestari, Neta; Lara Syaflin, Sylvia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem with this research is that students have difficulty understanding the material on the forms of cultural diversity in Indonesia, especially on the island of Sumatra, as well as the lack of use of learning media. This research aims to produce learning media for Indonesian cultural cards (kabusa) that are valid, practical and effective. The method used is the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The research results showed that the Indonesian cultural card learning media (kabusa) that was developed met the